A STUDY OF RELIGIOUS SYMBOLS ATTACHED TO THE FORMER TERRORIST CONVICTS’ FAMILY AS SEEN IN SOCIAL INTERACTION - Nihayaty, Arini Indah; Suyanto, Bagong; Sutinah, Sutinah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
This research discusses religious symbol attached to the former terrorist convicts’ family as seen in social interaction. The theory applied in this study is George Herbert’s the symbolic interactionism. This theory is used in analysing the phenomena in society because it is rooted in and focuses on the essence of humans as relational beings. This study is also reinforced by Erik H. Erikson's theory of psychosocial developmental stages and family sociology. The employed research method is qualitative method supported by interpretive paradigm. The data collection methods in this research are in-depth interview, observation, field notes, and documentation. The locations in the study are the areas of Surabaya (including Sidoarjo), Malang and Probolinggo, which are known as the hideout locations of JAD (Jamaah Asharut Daulah) terrorist network. This study concludes that former terrorist convicts and their families still strongly embrace the religious symbols in the process of social interaction. The radicalization that occurs within the family is classified as a discourse, not an action. The resilience should be embraced by these former convict families to strengthen their existence as well as prevent them from returning to their groups. The government and all stakeholders must continue to provide guidance to the families of former terrorist convicts.Keywords: Family; Psychosocial; Religious Symbols; Symbolic Interaction; Former Terrorist Convictsملخصتناقش هذه الدراسة الرموز الدينية للمدانين بالإرهاب السابقين وأسرهم. النظرية المستخدمة في هذه الدراسة هي تفاعل رمزي أشاعه جورج هربرت ميد. تُستخدم نظرية التفاعل الرمزي في تحليل أعراض المجتمع ، لأنها متجذرة في طبيعة البشر وتركز عليها ككائنات علائقية. هذه الدراسة مدعومة أيضًا بنظرية مراحل التطور النفسي والاجتماعي وعلم اجتماع الأسرة التي روج لها إريك إريكسون. الطريقة المستخدمة هي الطريقة النوعية ، باستخدام نموذج تفسيري. طرق جمع البيانات في هذه الدراسة من خلال المقابلات والملاحظات والملاحظات الميدانية والتوثيق المعمقة. تشمل المواقع التي شملتها الدراسة سورابايا (بما في ذلك سيدوارجو) ومالانج وبروبولينجو ، وهي أماكن اختباء لشبكة JAD الإرهابية (جماعة أشاروت دولاه). ونتيجة لذلك ، لا يزال المدانون السابقون بالإرهاب وعائلاتهم أقوياء في الحفاظ على الرموز الدينية ، وكلها تستخدم في عملية التنشئة الاجتماعية في المجتمع. يُصنَّف حاليًا احتمال حدوث التطرف داخل أنفسهم وعائلاتهم كشكل من أشكال الخطاب وليس الفعل. في هذا الموقف ، لا تزال هناك حاجة لتدخل من الحكومة وجميع أصحاب المصلحة حتى يمكن تقليل احتمالية التطرف.الكلمات المفتاحية: عائلة; نفسية اجتماعية; رموز دينية; تفاعل رمزي; مدانون إرهابيون سابقونABSTRAKPenelitian ini membahas tentang simbol-simbol keagamaan dari mantan narapidana teroris dan keluarganya. Teori yang dipakai dalam kajian ini adalah interaksi simbolik yang dipopulerkan George Herbert Mead. Teori interaksi simbolik digunakan dalam menganalisis gejala masyarakat, karena berakar dan berfokus pada hakekat manusia sebagai makhluk relasional. Kajian ini juga didukung oleh teori tahap perkembangan psikolososial dan sosiologi keluarga yang dipopulerkan Erik H. Erikson. Metode yang digunakan adalah kualitatif, menggunakan paradigma interpretif. Metode pengumpulan data dalam penelitian ini dengan wawancara mendalam, observasi, catatan lapangan, dan dokumentasi. Lokasi dalam penelitian meliputi wilayah Surabaya (termasuk Sidoarjo), Malang dan Probolinggo yang merupakan lokasi dari persembunyian jaringan teroris JAD (Jamaah Asharut Daulah). Hasilnya, mantan narapidana teroris dan keluarganya masih kuat dalam mempertahankan simbol-simbol keagamaan, yang semua itu digunakan dalam proses sosialisasi dalam masyarakat. Potensi radikalisasi yang terjadi dalam diri mereka dan keluarga saat ini tergolong dalam bentuk wacana bukan aksi. Dalam posisi ini, tetap diperlukan intervensi dari pemerintah dan semua pemangku kepentingan agar potensi radikalisasi itu benar-benar bisa diminimalkan.